Policultivo de litopenaeus vannamei (boone, 1931): uma revisão sistemática com meta-análise - Lima, David da Silva (Universidade Federal Rural do Semi-Árido, 2018)
Within aquaculture production, grows the polyculture method used for two or more species simultaneously within the same aquatic environment. The objective of this research was to evaluate the difference between survival and productivity of shrimp (Litopenaeus vannamei) between monoculture and polyculture, through a systematic review followed by meta-analysis of published studies. A set of twelve articles for survival and nine for productivity was used, after they have gone through a selection of eligibility and data extraction to summarize such information. The random model was used in both because of the heterogeneity of the data the fixed model would not be appropriate. To explain the heterogeneous data, subgroup analysis and meta-regression were used. The systematic review with the meta-analysis showed that there are no significant differences between the establishment of L.vannamei in monoculture and polyculture.. Projects focused on animal production need to use broader forms of research, in order to deepen academic knowledge and thus, have a return of new information to their environment
Keywords: Litopenaeus vannamei; carcinicultura; policultivo; meta-análise; Litopenaeus vannamei; shrimp culture; polyculture; meta-analysis; CIENCIAS AGRARIAS::ZOOTECNIA